1993
DOI: 10.1080/00223980.1993.9915543
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Life Satisfaction in Japan and Australia

Abstract: We examined the relationship between loneliness and life satisfaction in 121 residents of Fukoku, Japan, and 139 residents of Melbourne, Australia, using the Satisfaction With Life Scale (Diener, Emmons, Larsen, & Griffin, 1983) and the Revised UCLA Loneliness Scale (Russell, Peplau, & Cutrona, 1980). Australian subjects reported significantly less loneliness and significantly greater life satisfaction than Japanese subjects. A high inverse correlation was found between loneliness and life satisfaction in Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
1
36
0
9
Order By: Relevance
“…In some studies, negative relationships were found between loneliness and subjective well-being (Bramston, Pretty, & Chipuer, 2002;Chipuer, Bramston, & Pretty, 2003;Sharma, 2011) and loneliness and life satisfaction (Bugay, 2007;Çivitci, Çivitci, & Fiyakalı, 2009;Goodwin, Cook, & Yung, 2001;Kapıkıran, 2013;Kapıkıran & Yağcı, 2012;Mellor et al, 2008;Nickerson & Nagle, 2004;Salimi, 2011;Schumaker, Shea, Monfries, & Groth-Marnat, 1993;Yıldız, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, negative relationships were found between loneliness and subjective well-being (Bramston, Pretty, & Chipuer, 2002;Chipuer, Bramston, & Pretty, 2003;Sharma, 2011) and loneliness and life satisfaction (Bugay, 2007;Çivitci, Çivitci, & Fiyakalı, 2009;Goodwin, Cook, & Yung, 2001;Kapıkıran, 2013;Kapıkıran & Yağcı, 2012;Mellor et al, 2008;Nickerson & Nagle, 2004;Salimi, 2011;Schumaker, Shea, Monfries, & Groth-Marnat, 1993;Yıldız, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Margalit'e (2010) göre çocukluktaki yalnızlık, kişinin mevcut yaşam kalitesini etkileyen acı bir duygusal yaşantı olmasının yanısıra bireyin gelecekteki iyi oluşu için de gelişimsel bir risk oluşturmaktadır. Alan yazında yapılan çok sayıdaki çalışmada yalnızlık ile pozitif psikolojinin temel kavramları olan yaşam doyumu ve öznel iyi oluş arasında olumsuz yönde ilişkiler bulunmuştur (Ben-Zur, 2012;Bugay, 2007;Çivitci, Çivitci ve Fiyakalı, 2009;Goodwin, Cook ve Yung, 2001;Kapıkıran, 2013;Kapıkıran ve Yağcı, 2012;Mellor, Stokes, Firth, Hayash ve Cummins, 2008;Salimi, 2011;Shaheen, Jahan ve Shaheen, 2014;Schumaker, Shea, Monfries ve Groth-Marnat, 1993;Tuzgöl Dost, 2007;Yıldız, 2013Yıldız, , 2016Yılmaz ve Altınok, 2009). Bazı çalışmalarda ise yalnızlık ile benlik saygısı arasında olumsuz yönde ilişkiler bulunmuştur (Baran, Baran ve Maskan, 2015;Erözkan, 2009;Güloğlu ve Karaırmak, 2010;Shaheen vd., 2014).…”
unclassified
“…Loneliness has been associated with depression and suicide ideation 10 , lower life satisfaction 11 , elevated blood pressure levels 12 , increased stress hormone levels 13 and compromised immune system 14 . Loneliness has also been related to an increased tendency to experience subclinical and clinical hallucinations 15,16 and to nonclinical paranoid thinking 17,18 .…”
Section: Introductionmentioning
confidence: 99%